Design and Testing of an Offset Straw-Returning Machine for Green Manures in Orchards - Quanzhong Zhang; Jinfei Zhao; Xiaowen Yang; Ling Wang; Guangdong Su; Xinying Liu; Chuang Shan; Orkin Rahim; Binghui Yang; Jiean Liao (Agriculture)
In order to solve the problems of traditional orchard-specific green manure crushing and returning machines, such as the single operation effect, root system damage, unsustainable green manure growth, and low utilization rate, an offset crushing–furrowing–burying–straw-returning machine was designed for green manures in orchards. Based on quadratic regression combination experiments, the Discrete Element Method (EDEM) was used to construct a discrete element model simulating the deep furrowing and burying processes of the furrowing and soil-covering device, where the advance speed, plow-shaped furrowing blade rotation speed, and furrowing depth were considered as experimental factors and the coverage rate was taken as an evaluation index, and then simulation analyses were carried out to obtain experimental data; Design-Expert was used to perform ANOVA and RSM analyses, thus finding that its optimal working parameter portfolio consists of the advance speed of 42 m/min, the furrowing blade rotation speed of 300 r/min, and the furrowing depth of 190 mm, and that the coverage rate is 95.82% when this parameter portfolio is applied. Field experiments were conducted to validate the optimal parameter portfolio. The experimental results show that with an average coverage rate of 90.87% (4.95% away from the optimal value based on the simulation experiments on average), an average crushing length qualification rate of 91.24%, and an average root system damage rate of 5.6%, this device is applicable for its operation conditions. The development of this machine and the construction of its parameter model can provide a certain reference value for developing and optimizing related machines including green manure-returning machines.